Is Justice a Fixed Point?. Issue 2 (15th June 2021) - Schaefer, Alexander
Abstract: Following the work of John Rawls, political theorists have fixated on the comparative stability of different equilibrium states of justice. This article identifies a crucial gap in this literature, namely, the lack of attention paid to nonequilibrating systems. Drawing on Kakutani's theorem, I present plausible cases in which society will fail to exhibit any equilibrium states of justice. An important implication for political theory is that, rather than focusing exclusively on stable equilibria, theorists should examine dynamic processes of justice, which need not exhibit equilibrating forces. To this end, a concept more useful than stability is that of robustness, or the ability of a system to maintain general desiderata in the face of an evolving conception of justice.